2019
DOI: 10.1186/s12866-019-1575-7
|View full text |Cite
|
Sign up to set email alerts
|

Peptidoglycan-type analysis of the N-acetylmuramic acid auxotrophic oral pathogen Tannerella forsythia and reclassification of the peptidoglycan-type of Porphyromonas gingivalis

Abstract: Background Tannerella forsythia is a Gram-negative oral pathogen. Together with Porphyromonas gingivalis and Treponema denticola it constitutes the “red complex” of bacteria, which is crucially associated with periodontitis, an inflammatory disease of the tooth supporting tissues that poses a health burden worldwide. Due to the absence of common peptidoglycan biosynthesis genes, the unique bacterial cell wall sugar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…After digestion of PGN with the N -acetylmuramidase mutanolysin, the PGN composition was determined by LC-MS, revealing the presence of GlcNAc-MurNAc-peptides (G-M-tri/tetra) and dimers thereof as typical digestion products. For E. coli [ 13 ], as well as T. forsythia and P. gingivalis , the stem peptide is composed of Ala, Glu, m- DAP and Ala, referring to the PGN-type A1γ, as published previously [ 16 ]. Regarding the PGN of F. nucleatum , Vasstrand et al reported that lanthionine instead of m -DAP occurs in the stem peptide [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After digestion of PGN with the N -acetylmuramidase mutanolysin, the PGN composition was determined by LC-MS, revealing the presence of GlcNAc-MurNAc-peptides (G-M-tri/tetra) and dimers thereof as typical digestion products. For E. coli [ 13 ], as well as T. forsythia and P. gingivalis , the stem peptide is composed of Ala, Glu, m- DAP and Ala, referring to the PGN-type A1γ, as published previously [ 16 ]. Regarding the PGN of F. nucleatum , Vasstrand et al reported that lanthionine instead of m -DAP occurs in the stem peptide [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…This study sought to investigate how the periodontal pathogen T. forsythia can benefit from cohabiting biofilm bacteria to overcome its MurNAc auxotrophy . T. forsythia possesses a conventional Gram-negative PGN of the A1γ-type [ 16 ]; thus, it is conceivable to assume that the bacterium procures the essential PGN building block MurNAc from the oral biofilm consortium. Currently it is unknown, which sources of MurNAc likely available in the oral cavity T. forsythia can access.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations